2021
DOI: 10.3390/ma14092280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ZEBRA Battery Module under the Peak-Shaving Duty Cycles

Abstract: With the recent rapid increase in demand for reliable, long-cycle life, and safe battery technologies for large-scale energy-storage applications, a battery module based on ZEBRA battery chemistry is extensively evaluated for its application in peak shaving duty cycles. First, this module is tested with a full capacity cycle consisting of a charging process (factory default) and a discharging process with a current of 40 A. The battery energy efficiency (discharge vs. charge) is about 90%, and the overall ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Relatively high specific energy (120 W h kg −1 ) can be achieved at 300 °C with energy efficiency varying from 90 to 95%. 163 Besides, Shamim et al 156 reported a 90% energy efficiency at 265 °C for a ZEBRA battery module (48TL200) from FzSoNick with promising stability (a degradation rate of 0.0046%/cycle over 150 cycles). In 2022, Zhu et al 157 reported, as shown in Fig.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively high specific energy (120 W h kg −1 ) can be achieved at 300 °C with energy efficiency varying from 90 to 95%. 163 Besides, Shamim et al 156 reported a 90% energy efficiency at 265 °C for a ZEBRA battery module (48TL200) from FzSoNick with promising stability (a degradation rate of 0.0046%/cycle over 150 cycles). In 2022, Zhu et al 157 reported, as shown in Fig.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…150 As in room temperature electrolytes, metallic negatrodes, such as Li, Na, Mg, Al and Fe, have been investigated extensively in molten salt batteries. [151][152][153][154][155][156][157][158][159][160][161][162] For instance, Giordani et al 152 reported a Li-O 2 battery with 95% energy efficiency achieved in a molten LiNO 3 -KNO 3 eutectic at 150 °C. However, the cycling stability was poor (<50 cycles, 2.6 mA h cm −2 at 0.6 mA cm −2 ), due to the oxidation of carbon and consequent formation of Li 2 CO 3 at the positrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the Na-based batteries considered for large-scale grid storage applications, molten sodium-metal batteries have recently regained popularity mostly due to the recent advancements in the development of intermediate-temperature molten sodium-metal batteries (SMBs), including Na-metal halide (Na-MH) and Na-S batteries based on a β"-Al 2 O 3 solid electrolyte (BASE) [3,4,[20][21][22][23]. BASE electrolytes have a high ionic conductivity (∼1 and 250 mS cm −1 at 25 and 300 • C, respectively), an outstanding mechanical stability, and a wide electrochemical window.…”
Section: Molten Sodium-metal Batteriesmentioning
confidence: 99%
“…Originally, SMBs were based on molten Na-S batteries or Na-MH batteries operating at around 300 • C with β"-Al 2 O 3 solid electrolyte (BASE). While both types of molten SMBs are of technological interest and have been commercialized, Na-MH batteries, such as Na-NiCl 2 batteries, are particularly promising due to their inherent safety in terms of cell failure relative to Na-S batteries, the less corrosive active materials compared to S and polysulfides, and easier cell assembly in the discharged state without handling hazardous Na metal and metal halides [3,4]. Unfortunately, the widespread adoption of both Na-S and Na-MH batteries in grid-level energy storage has been dwarfed by the safety concerns associated with their high operation temperature, plus the unstoppable emergence of Li-ion batteries.…”
Section: Introductionmentioning
confidence: 99%